Testing the Depending Factors of Using the Digital Currency - Ammar W. M. Sheet; Kalid Abdul-Hammed Abdel-Majed; Muhammed K. Rashad; Zaid Saad Ismail (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
In the modern processes that happened in online with evolution of technology Digital currencies was effect on the process with new marketing exchange, selling, investment etc., but still not depend because lack of use it, security issue and the risks associated when dealing with hackers and information leakage. In this research we select Knowledge university and we distribute about (40) questioner and we receive all. Data have been collected from the questioner and analyzed. After analysis, significant results of both dependent and independent variables have been obtained. From the results, we can get an idea about the policies and usage of DC affect on the decision to use it.